Sensory-Analytical Comparison of the Aroma of Different Horseradish Varieties (Armoracia rusticana) - Kroener, Eva-Maria; Buettner, Andrea (Frontiers in Chemistry, 2018)
Horseradish (Armoracia rusticana) is consumed and valued for the characteristic spicy aroma of its roots in many countries all over the world. In our present study we compare six different horseradish varieties that were grown under comparable conditions, with regard to their aroma profiles, using combined sensory-analytical methods. Horseradish extracts were analyzed through gas chromatography-olfactometry (GC-O) and their aroma-active compounds ranked according to their smell potency using the concept of aroma extract dilution analysis (AEDA). Identification was carried out through comparison of retention indices, odor qualities and mass spectra with those of reference substances. Besides some differences in relative ratios, we observed some main odorants that were common to all varieties such as 3-isopropyl-2-methoxypyrazine and allyl isothiocyanate, but also characteristics for specific varieties such as higher contents for 3-isopropyl-2-methoxypyrazine in variety Nyehemes. Moreover, three odorous compounds were detected that have not been described in horseradish roots before.